Manajemen Pendidikan Inklusif melalui Penerapan Manajemen Kelas Responsif bagi Anak Berkebutuhan Khusus - Zaini, Ansori; Safrilana, Yuda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses inclusive education management through the implementation of responsive classroom management for students with special needs. Inclusive education in regular schools requires adaptive, equitable, and responsive learning management to address the diverse needs of students, making effective classroom-level management essential. This study aims to analyze the concepts, principles, and strategies of responsive classroom management as part of inclusive education management and its role in supporting effective learning for students with special needs. The research employed a qualitative approach using a library research method. Data were obtained through a systematic review of relevant literature, including academic books, national and international journal articles, educational regulations, and policy documents related to inclusive education and classroom management. Data analysis was conducted by reviewing, categorizing, comparing, and synthesizing conceptual findings from the literature to develop a comprehensive and systematic understanding. The findings indicate that responsive classroom management in inclusive education is characterized by the principles of equity and individualization, differentiated instruction, structured and consistent classroom routines, positive behavior reinforcement, multiparty collaboration, and the use of adaptive learning resources. The application of responsive classroom management contributes to the creation of a conducive learning environment, increased student engagement, and the support of academic as well as socio-emotional development of students with special needs. This study concludes that responsive classroom management plays a strategic role in strengthening inclusive education management and should be used as a foundational approach in planning and managing learning processes in inclusive schools.